Silver Chloride Encapsulation-Induced Modifications of Raman Modes of Metallicity-Sorted Semiconducting Single-Walled Carbon Nanotubes. (1st April 2018) - Kharlamova, M. V.; Kramberger, C.; Mittelberger, A.; Yanagi, K.; Pichler, T.; Eder, D.
Abstract : The internal channels of semiconducting single-walled carbon nanotubes (SWCNTs) were filled with silver chloride. The filling was confirmed by high-resolution scanning transmission electron microscopy. The filling-induced modifications of Raman modes of SWCNTs were analyzed. The fitting of the radial breathing mode (RBM) and G-bands of Raman spectra of the pristine and filled nanotubes with individual components allowed analyzing in detail the influence of encapsulated silver chloride on the electronic properties of different diameter nanotubes. The analysis of the RBM-band allowed revealing the changes in resonance excitation conditions of SWCNTs upon filling. The analysis of the G-band allowed concluding about p -doping of nanotubes by incorporated silver chloride accompanied by charge transfer from nanotubes to the inserted salt.